Mitochondrial Fragmentation in a High Homocysteine Environment in Diabetic Retinopathy - Renu A. Kowluru; Ghulam Mohammad (MDPI AG, 2022)
Diabetic patients routinely have elevated homocysteine levels, and due to increase in oxidative stress, hyperhomocysteinemia is associated with increased mitochondrial damage. Mitochondrial homeostasis is directly related to the balance between their fission and fusion, and in diabetes this balance is disturbed. The aim of this study was to investigate the role of homocysteine in mitochondrial fission in diabetic retinopathy. Human retinal endothelial cells, either untransfected or transfected with siRNA of a fission protein (dynamin-related protein 1, Drp1) and incubated in the presence of 100 μM homocysteine, were analyzed for mitochondrial fragmentation by live-cell microscopy and GTPase activity of Drp1. Protective nucleoids and mtDNA damage were evaluated by SYBR DNA stain and by transcripts of mtDNA-encoded ND6 and cytochrome b. The role of nitrosylation of Drp1 in homocysteine-mediated exacerbation of mitochondrial fragmentation was determined by supplementing incubation medium with nitric-oxide inhibitor. Homocysteine exacerbated glucose-induced Drp1 activation and its nitrosylation, mitochondrial fragmentation and cell apoptosis, and further decreased nucleoids and mtDNA transcription. Drp1-siRNA or nitric-oxide inhibitor prevented glucose- and homocysteine-induced mitochondrial fission, damage and cell apoptosis. Thus, elevated homocysteine in a hyperglycemic environment increases Drp1 activity via increasing its nitrosylation, and this further fragments the mitochondria and increases apoptosis, ultimately leading to the development of diabetic retinopathy.